Use of continuous horizontal mattress suture techniques in microsurgery: An experimental study in rats - EROL, BÜLENT (W B SAUNDERS CO, 2005)
Purpose: The purpose of this study was to determine whether the continuous horizontal mattress suture technique can replace the continuous simple suture technique and to compare the results with other microvascular suture procedures. Methods: Sixty-four femoral arteries of 32 Sprague-Dawley rats were used in this study. The animals were divided equally into 4 groups with 16 anastomoses in each group. The arteries (6.8-1.0 mm diameter) were anastomosed by using the continuous horizontal mattress suture technique in group I, interrupted horizontal mattress suture technique in group II, simple interrupted suture technique in group III, and simple continuous suture technique in group IV. At the end of the anastomosis time, leakage, and patency were assessed and graded in all groups. On the 14th day after surgery the rats were killed and 5 patent specimens from each group were examined under light microscopy for histology. One specimen from each group was prepared for scanning of the endothelial surface under electron scanning microscopy. Results: Group I anastomoses were performed the most quickly. Groups I and III anastomoses had 100% patency rates. Under light microscopy the edge eversion was apparent consistently and under electron microscopy all endothelial surfaces were intact and no suture material was seen in groups I and II. In group III some suture material was covered by endothelial cells and lumen surfaces were torn; endothelization also was rough compared with groups I and II. In group IV suture material was seen in the lumen because of a loose suture knot. The endothelium also was not regular. Conclusions: The horizontal mattress suturing technique is the only technique in which the suture material never contacts the lumen. Continuous horizontal mattress suture technique is superior to the other microvascular procedures and is the safest and fastest procedure for microvascular anastomosis in rats.
Keywords: microvascular; anastomosis; suturing; horizontal mattress; interrupted; continuous; MICROVASCULAR ANASTOMOSIS; DIAMETER